Peutz-Jeghers syndrome: need for early screening. Issue 1 (13th December 2018) - Khanna, Kashish; Khanna, Vikram; Bhatnagar, Veereshwar
Abstract : Peutz-Jeghers syndrome (PJS) is an autosomal dominant cancer-predisposing condition characterised by intestinal hamartomatous polyps and distinct melanin depositions in skin and mucosa. Small intestinal cancer in patients with PJS usually presents by the third decade. A 7-year-old-PJS boy presented with recurrent episodes of colicky abdominal pain and melena requiring repeated blood transfusions. Abdominal CT scan revealed multiple jejunal polyps with jejunoileal intussusception. On exploration, the intussuscepted bowel was resected along with its mesentery and anastomosed. Simultaneously, multiple enterotomies with resection of palpable polyps were performed. The resected bowel showed well-differentiated stage 2A adenocarcinoma with clear resected margins. Postoperatively, the complaints were relieved. On follow-up, he was asymptomatic and is now on yearly cancer surveillance. This is probably the youngest reported case of small bowel cancer in PJS.